ANALISIS KINERJA KEUANGAN PERUSAHAAN MENGGUNAKAN ANALISIS RASIO KEUANGAN DAN COMMON SIZE (Studi PT. Sekar Bumi Tbk. , PT. Sekar Laut Tbk. dan PT. Mayora Indah Tbk. Periode 2011 - 2014 periode 2011 - 2014) - Lupitasri, Nur Indah; Hidayati, Cholis (Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTPT. Sekar Bumi Tbk. PT Sekar Laut, Tbk. and PT Mayora Indah Tbk is some food company that manufactures and sells consumer goods - day. The three companies are competing to increase its profit and to conduct its business expansion. Is inseparable from the three companies that are required to assess each year whether the financial statements are already meet the standard conditions of the financial performance of companies using financial statement analysis. For that conducted research at PT. Sekar Bumi Tbk. PT Sekar Laut, Tbk. and PT Mayora Indah Tbk with the aim of analyzing the results of the company's financial performance when seen from the analysis of the financial statements of these companies. The financial statements of the three companies are measured using financial ratios of liquidity ratios, activity ratios, solvency ratios and profitability ratios as well as using common size analysis. From the analysis conducted is as follows ratio of the financial statements. Sekar Bumi Tbk. PT Sekar Laut, Tbk. and PT Mayora Indah Tbk shows the average - average financial performance is good. Keyword: Financial Statement Analysis, Financial Performance